Effect of high-intensity submaximal work, with or without rest, on subsequent VO2max - Judelson, D. A.; Rundell, K. W.; Beck, K. C.; King, T. M.; Laclair, K. L. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: In practice, tests of maximal oxygen uptake (.VO2max) are often preceded by a lactate profile, a highly intense but submaximal exercise bout. The .VO2max response to preceding high-intensity submaximal exercise, with or without a rest period, has not been determined. If .VO2max is limited after a lactate profile, exercise-induced hypoxemia (EIH) may explain the deficit. The purposes of this study were to: 1) examine the effects of high-intensity submaximal exercise, with or without rest, on subsequent .VO2max; and 2) evaluate the role of EIH in causing any observed changes. METHODS: Ten healthy, well-trained, male cross-country skiers (age = 20.5 +/- 4.7 yr, height = 181.6 +/- 6.0 cm, mass = 72.1 +/- 5.7 kg) completed three exercise trials: an incremental run to fatigue (MAX), MAX preceded by a high-intensity submaximal run (lactate profile) and a 20-min rest period (discontinuous protocol [DC]), and MAX preceded by a high-intensity submaximal exercise run with no rest (continuous protocol [C]). .VO2max, minute ventilation, and arterial oxygen saturation were measured throughout, and diffusion capacity was evaluated 2 min postexercise. RESULTS No significant between trial differences were observed, although the difference between .VO2max determined during the MAX trial (62.7 +/- 6.7 mL.kg-1.min-1) and during the DC trial (58.3 +/- 4.4 mL.kg-1.min-1) approached significance (P = 0.059). DC .VO2max responses could be separated into two groups: five responders whose .VO2max suffered during the DC trial (decreased >7.5% from MAX) and five nonresponders, whose .VO2max was unaffected by preceding submaximal exercise and a rest period. Responders showed greater aerobic capacity during the MAX trial. CONCLUSION: .VO2max is significantly reduced in approximately 50% of cross-country skiers when a maximal exercise test is preceded by high-intensity submaximal exercise and a 20 min rest period; the role of EIH in causing these reductions is unclear.